2017
DOI: 10.5604/12321966.1232762
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor performance of Polish Air Force cadets after 36 hours of survival training

Abstract: Introduction and objective. The aim of the study was to determine changes in the fitness level among students of the Main Fire Service School during 3-year's education. Methods. A total of 75 male and 5 female students took part in the study. Fitness level measurements were carried out before beginning the studies (Measurement 0) and after the 1 st , 2 nd and 3 rd years at the school (Measurement 1, 2, 3). The following tests were performed to estimate level of physical fitness for men: pull-ups on a bar, a 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
1
21
0
4
Order By: Relevance
“…The observed decline in handgrip strength has been attributed to either a decrement in muscle fibre recruitment or an alteration in motor unit firing frequency following SD [43]. No restoration in handgrip strength was reported following a 7-8 h sleep recovery period [35] or over 3 post-trial recovery days [43]. These findings However, these findings may also be attributed to the modest SR protocols implemented (i.e.…”
Section: Sleep Loss and Muscular Strengthmentioning
confidence: 91%
See 1 more Smart Citation
“…The observed decline in handgrip strength has been attributed to either a decrement in muscle fibre recruitment or an alteration in motor unit firing frequency following SD [43]. No restoration in handgrip strength was reported following a 7-8 h sleep recovery period [35] or over 3 post-trial recovery days [43]. These findings However, these findings may also be attributed to the modest SR protocols implemented (i.e.…”
Section: Sleep Loss and Muscular Strengthmentioning
confidence: 91%
“…More recently, some studies have investigated the effect of sleep loss on both the performance and physiological responses to aerobic exercises. For example, Tomczak et al [35] examined the heart rate (HR) response and time to completion of a 1-mile walk test following 36 h of SD combined with moderate physical activity in air force cadets. Despite no significant change in the time to completion of the 1-mile walk test, HR at completion was significantly lower following the SD protocol (148±6 to 132±3 bpm).…”
Section: Sleep Loss and Aerobic Performancementioning
confidence: 99%
“…The number of works in the literature in which the subject is dealt with is scarce, and most often they concern the actions of soldiers [3,4,5,6,7,8]. Several studies show the results of research conducted during survival training involving civilian participation.…”
Section: Introductionmentioning
confidence: 99%
“…Gawda et al have demonstrated that change in sEMG amplitude during isometric exercise could be related to muscles fatigue [17]. The use of various indices [18] and those based on sEMG amplitude, as an objective indicators of the efficacy of training process in athletes and motor programming phenomenon in humans requires further research. In the opinion of the authors of the presented study, the microgenetic theory which describe motor programming on the basis of findings in modern neurosciences (i.e., from gene expressions, electrical and chemical language of the brain, endomarkers, neuromarkers to behaviour), might be helpful in interpreting the efficacy of the training process and motor programming phenomenon in athletes living in rural and urban areas [19,20].…”
Section: Discussionmentioning
confidence: 99%